Моделювання напрямленого дистанційного захисту лініі електропередач в програмному комплексі PSCAD\EMTDC - Волохін, Віталій Васильович; Петровский, М. В.; Шевченко, Сергій Юрійович; Іванов, О. О.; Іванов, С. О.; Ігнатова, О. І. (НТУ "ХПІ", 2016)
Моделювання напрямленого дистанційного захисту лінії електропередач реалізоване в програмному комплексі PSCAD\EMTDC, а також порівняно дві характеристики спрацювання дистанційного органу, а саме кругову і багатокутну. Розроблений алгоритм пускового органу, який завдяки контролю векторного приросту струмів зворотної послідовності запобігає фальшивим спрацюванням при коливаннях електричної системи і асинхронному ході генераторів.

Distance protection is used in networks of complex configuration, which for reasons of safety and sensitivity cannot be used more simple overcurrent. This article demonstrate detailed distance protection scheme of power lines. Data are given about comparison of the circular and polygonal protection zone. The algorithm proposed in this paper prevents false triggered distance protection in a mode of asynchronous course, and swings in power system. It is show that the response time of the distance protection with polygonal protection zone response time is less than the distance protection with a circular protection zone. The simulation of the system is done by using PSCAD/EMTDC software
Modeling directional distance protection power lines in the software package PSCAD\MTDC
Keywords: електроенергетичні системи; дистанційний орган; пусковий орган; коливання; асинхронний хід; modeling; distance protection; remote organ; starting body; fluctuation; induction course